What explains public transport use? Evidence from seven European cities. (December 2020) - Gascon, Mireia; Marquet, Oriol; Gràcia-Lavedan, Esther; Ambròs, Albert; Götschi, Thomas; Nazelle, Audrey de; Panis, Luc Int; Gerike, Regine; Brand, Christian; Dons, Evi; Eriksson, Ulf; Iacorossi, Francesco; et al.
Abstract: Background: the relationships between the built environment characteristics and personal factors influencing public transport use and the ways they interact are not well understood. Objective: we aim to advance the understanding of the relationship between built environment and frequency of public transport use in seven European cities, while accounting for other factors, such as individual values and attitudes. Methods: in this population-based cross-sectional study, we collected information on mobility behaviour including frequency of public transport use, individual characteristics, and attitudes towards transport, environment and health issues (N = 9952). Home and work/study built environment characteristics were determined with GIS-based techniques. We also applied factor and principal component analyses to define profiles of potential correlates. Logistic regression analyses for each frequency category of public transport use (1–3 days/month, 1–3 days/week, and daily or almost daily), using as reference "never or less than once a month", were applied. City was included as random effect. Results: Over all, a large percentage of participants reported daily or almost daily public transport use for travel (40.5%), with a wide range across cities (from 7.1% in Örebro to 59.8% in Zurich). Being female, highly educated, a student, or not working increased the odds of higher frequency of using public transport, while having access to a car and/or a bike reduced the odds. Living or working in high-density areas was associated with higher frequency of public transport use, while living or working in low-density areas was associated with lower frequency (1–3 days/month or 1–3 days/week). We observed interactions between built environment characteristics and having access to a car and/or a bike. For instance, greater distance between the residential and the work or study address increased the odds of higher frequency of public transport use, except among participants who owned a car but not a bike. Regarding individual values and attitudes towards public transport use, valuing lower travel cost and shorter travel time was associated with daily or almost daily public transport use, while valuing low exposure to air pollution, personal health benefits while travelling, as well as flexibility and predictability, were associated with more sporadic use. Conclusions: We demonstrate, using one of the largest population-based comprehensive multi-city surveys across European cities with varying social and physical contexts, that dense urban environments, reliable and affordable public transport services, and limiting motorized vehicles in high density areas of the cities will help achieve much needed promotion of public transport use. Highlights: Dense areas with mixed-land uses promote daily public transport use. Urban sprawl is associated with sporadic public transport use (few times a week or a month). We observed interactions between built environment characteristics and access to a car/bike. Fast and reliable service at affordable prices are key correlates of public transport use. Public transport users also value its environmental and health benefits.